Долог наш путь: повести / Владимир Маканин - Маканин Владимир Семенович (Вагриус, 1999)
Экземпляры: аб. (2001) / Инвентарный номер: 43077 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: М 15 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44